Subcellular Sites Involved in Lipid Synthesis in Saccharomyces cerevisiae - Klein, Harold P. (1967)
When the crude ribosomal fraction of Saccharomyces cerevisiae was separated into “light” and “heavy” fractions, fatty acid synthetase was concentrated in the former, whereas acetyl-Coenzyme A synthetase, fatty acid “desaturase,” and squalene oxidocyclase were found in the latter. The “desaturase” sedimented with the ribosomal material and was not solubilized by low concentrations of sodium deoxycholate (DOC). The other two systems found in the “heavy” fraction sedimented with the membranes, but, upon solubilization of the membranes by DOC, these enzyme systems remained as particles.